Polycyclic Aromatic Hydrocarbons (PAHs) in water of Al-Kahlaa River in Missan Province, Iraq - Salih Hassan Jazza; Abdul Hussain Y. Al-Adhub; Hamid T. Al-Saad (Marine Science Department Diponegoro University, 2016)
The present study was performed to have knowledge of Polycyclic Aromatic Hydrocarbonspollution status in water. The samples were collected during two seasons (winter and summer 2012 ,2013) from four different stations) Al-Magideh, Treatment unit, Al-Husaichi and Al-Zubair) distributed along Al-KahlaaRiver in Missan province, in addition to reference station lies on the Tigris river before 25 Km from entering to Amara city. The concentrations of PAHs were determined in by using capillary Gas Chromatography. Results of the present study revealed that the total concentrations of PAHs in dissolved fraction ranged from 0.739 ng.l-1 in Reference station to 1.974 ng.l-1 in Treatment unit during winter, and from 0.300 ng.l-1 in Reference station to 1.125 ng.l-1 in Treatment unit during summer, while in the particulate fraction they varied from 0.79 ng.g-1 dry weight in Reference station to 24.42 ng.g-1 dry weight in Treatment unit during winter, and from 4.369 ng.g-1 dry weight in Reference station to 10.545 ng.g-1 dry weight in Al-Husaich during summer. It had been noticed that there were a predominance of high molecular weight PAHs on low molecular weight, while BaA/(BaA+Chr) ratio in water ranged from 0.218 to 0.804. InP/(InP+BghiP) ratio ranged between 0 and 0.578,whereas Fl/Pyratio ranged between 0.150 and 2 ,this give an indication of the origin of PAHs compounds in water which were mainly pyrogenic and few from them petrogenic. Keywords: polycyclic aromatic hydrocarbons, PAHs, water, pollution